2019
DOI: 10.2478/remav-2019-0020
|View full text |Cite
|
Sign up to set email alerts
|

Housing Needs of Older People in Poland as Exemplified by the Warsaw, Poznań and Szczeciń Urban Areas

Abstract: Due to an ageing population, local governments are facing new challenges in the field of addressing the housing needs of older people. Seniors are not a homogeneous group; three basic categories may be distinguished in terms of independence level and the resulting needs. The first category would include independent people, the second one - the elderly with limited independence, and in this case it is necessary to adapt their dwellings to the needs of people with partial disabilities, e.g. dedicated housing. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…This also refers to the group of senior citizens. The number of people at advanced age, i.e., 85 and over, will increase, which is associated with the aging of the birth cohorts recorded during the demographic summit after World War II [28]. Developed societies will be increasingly burdened with providing social care for the aging and growing part of the population.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This also refers to the group of senior citizens. The number of people at advanced age, i.e., 85 and over, will increase, which is associated with the aging of the birth cohorts recorded during the demographic summit after World War II [28]. Developed societies will be increasingly burdened with providing social care for the aging and growing part of the population.…”
Section: Discussionmentioning
confidence: 99%
“…The research conducted in three Polish cities (Warsaw, Szczecin, and Poznań) [28] showed that when asked about their readiness to change their current apartment, the respondents provided the following answers: nearly 70% of those living in Poznań marked “definitely not’”, while for Warsaw and Szczecin, this answer was selected by approximately half of the respondents. A quarter of the respondents from Szczecin would be willing to change their place of residence, but only if it was in the same estate/in the same neighbourhood; in Warsaw, the respective share was 16.3%, whereas in Poznań, it was 8%.…”
Section: The Willingness To Move From An Apartment/house To An Apamentioning
confidence: 99%
See 2 more Smart Citations
“…Some recent research on the identification of housing needs was prepared by Przybyła et al [17] and Iwański et al [18]. They used survey research in order to identify the housing preferences of the respondents.…”
Section: Overview Of Existing Studiesmentioning
confidence: 99%